Examine the association between self-employment and return migrants in Ethiopia: Evidence from Gondar city youth returnees - Endalew Terefe Alene (Journal of Innovation and Entrepreneurship, 2023)
Purpose: This study attempted to contribute to the existing literature on return migration by framing the discussion within the association between self-employment and returning migrants in the context of Ethiopia particularly on Gondar city youth returnees. Design/methodology/approach: The study has used a combination of cross-sec- tional and descriptive research design with a quantitative approach. Quantitative data from 195 youth returnees using a survey questionnaire were employed to address the study objectives. A Census sampling strategy was employed to select study partici- pants. To test the study hypothesizes, a χ2 test was implemented to show the associa- tion between independent and dependent variables. Findings: The findings of this study showed that there is no association between self-employment and return migrants. More specifically, the study results revealed that sectoral and occupational experience gained from abroad do not help return migrants for new business formation. Research limitations/implications: This study which was focused only on self- employed return migrants where comes from Saudi Arabia, likely does not represent the whole return migrants from abroad. In addition, this study does not include all independent variables that influence the self-employment of return migrants. It only considers occupational and sectoral experience. To understand comprehensively, future research will do by considering all indicators of self-employment of return migrants and also make a comparative analysis between urban and rural return migrants' possibility to become self-employed. Practical implications: Return migration is one of the demographic phenomena in the world which needs attention from government and non-government organiza- tions. Taking into account this, the paper will serve as an input for policymakers and local officials to consider self-employment carefully to support returnees' sustainable entrepreneurial performance and economic growth. It will also help officials to under- stand some of the challenges that self-employed returnees have been faced including the provision of working area, formal credit, and pieces of training consistent with the experience brought from abroad and tax incentives. Originality/value: Studies on youth return migration in sub-Saharan Africa countries are limited and this study will contribute to the return migration literature with an attempt to examine the association between self-employment and return migration in the context of Ethiopia. Accordingly, it examines the relationship between self-employ- ment among youth return migrants by taking sectoral and occupational experience as major indicators.
Keywords: 650; Association; Gondar city; Occupational experience; Return migration; Sectoral experience; Self-employment